Mencermati Dinamika Perkembangan Model Manajemen Pemerintahan Daerah :Dari Sentralisasi Ke Desentralisasi - Gedeon, Hendrikus Tri Wibawanto (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2006)
The model of local government management in Indonesia, if it was investigated be seen that its development experiences enough interesting dinamisc, both sentralization model and desentralization model. In this article, the writer try to pay attention close to development the local government management, with focus its analysis from ORBA Regime to Reform Regine. In this final analysis will be recommended a local government management model that is assumed appropriate to today condition.